Copper-Catalyzed Enantioselective O,S‑Rearrangement of Propargylic Xanthates: Efficient Synthesis of Chiral Propargylic Sulfur Compounds - Wang, Cheng; Xiao, Mengdie; Li, Wei; Cheng, Li-Jie (ACS catalysis, 2024)
A base-free, copper-catalyzed enantioselective O,S-rearrangement of propargylic xanthates has been developed to enable efficient synthesis of chiral propargylic sulfur compounds in high yields with good enantioselectivities. This method allows for the use of a variety of propargylic xanthates containing primary, secondary, and tertiary alkyl substituents and tolerates a broad range of functional groups. The synthetic utility of this method has been demonstrated through various downstream transformations of the resulting products to diverse enantioenriched organosulfur compounds. Mechanistic studies suggest the pseudo-intramolecular nucleophilic attack of a sulfur anion to a copper–allenylidene species is likely involved for the C–S bond formation.